(untitled) (Bangladesh Journal of Medical Science, 2021)
Objective: The study was designed to evaluate the efficacy of Cyriax physiotherapy versus Cyriaxand Low Level Laser Therapy to compare these techniques in reducing pain and improving gripstrength in patients with lateral epicondylitis. Methodology: The study population included 30patients of lateral epicondylitis (signs and symptoms present for more than 6 weeks) diagnosedin outpatient and indoor facilities of MM Hospital, Mullana. The subjects were selected bymeans of simple random sampling. After fulfilling the inclusion and exclusion criteria, thepatients were randomly allocated in two groups: Group A and Group B. Group A received cyriaxphysiotherapy alone whereas Group B patients were subjected to combined Cyriax and low levelLaser therapy. Baseline measurements of pain and grip strength were taken before treatmentand then at 3 weeks respectively. Results: Our findings showed that there was significantlyhigher improvement in pain and grip strength in Group B (patients receiving combination ofcyriax therapy with low dose laser therapy) as compared to Group A (p<0.05). Conclusion:Cyriax physiotherapy and low level laser therapy were effective in reducing pain and improvinggrip strength after the treatment sessions. But benefits of cyriax physiotherapy with low levellaser therapy in lateral epicondylitis patients are significantly higher as compared to cyriaxphysiotherapy alone over a three week period. Hence, cyriax with low level laser therapy isproved to be a better treatment. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.356-360